Worker flows in the European Union during the Great Recession - Jose Maria Casado; Cristina Fernandez; Juan F. Jimeno (European Central Bank (ECB), 2015)
We measure the contribution of worker flows across employment, unemployment, and non-participation to the change in unemployment in eleven EU countries during the period 2006-2012, paying special attention to which socio-demographic groups in each of the countries were mostly affected by job creation and job destruction during the crisis. We find that age, to a larger extent than educational attainments, is the main determinant of flows from employment into unemployment, particularly in those countries where unemployment increased by most. Secondly, we highlight some institutional features of the labour market (employment protection legislation, unemployment insurance, and the incidence of active labor market policies) that help to explain the cross-country differences in flows between employment and unemployment and in their socio-demographic composition. Finally, we examine if the crisis has led to some employment reallocation across sectors, finding that, so far, there is no clear evidence in favor of cleansing effects.
Keywords: J6; E24; C25; 330; Great Recession; Labour Flows; Labour Market Institutions; Unemployment